Efektivitas metode Drill untuk meningkatkan keterampilan merangkai Bloom Box Acrylic pada peserta didik disabilitas fisik - Dewi, Ratih Ratna; Budi, Setia; Ardisal, Ardisal; Safaruddin, Safaruddin (Borobudur Educational Review, 2025)
This research is motivated by the problem of students with physical disabilities who have not been able to assemble acrylic bloom boxes. The study aims to prove that the drill method is effective in improving the skills of assembling acrylic bloom boxes in students with physical disabilities at SLB YPAC West Sumatra. The study used an experimental research type in the form of a single subject research (SSR) with an A-B design. The subject of this study was one student with physical disabilities in grade VIII of SLB YPAC West Sumatra. The study was conducted in July 2025-August 2025. The data collection techniques used in this study involved interviews and tests. The data analysis technique used was visual graphic analysis. The results showed that in the baseline condition (A) the percentage results were 33%, 33% and 33%. In condition (B) the percentage results were 42%, 47%, 61%, 71%, 76%, 80%, 85%, 90%, and 90%. Based on the data analysis that has been done, it was found that the use of the drill method is effective in improving the skills of assembling acrylic bloom boxes in students with physical disabilities. The implications of the results of this study indicate that the drill method is effective in improving the skills of assembling acrylic bloom boxes in students with physical disabilities. Teachers can use the drill method consistently in learning skills, as well as modify the media and steps according to the individual needs of students.